2009
DOI: 10.1186/1471-2164-10-491
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of pseudorabies virus gene expression by real-time quantitative RT-PCR assay

Abstract: Background: Pseudorabies virus (PRV), a neurotropic herpesvirus of pigs, serves as an excellent model system with which to investigate the herpesvirus life cycle both in cultured cells and in vivo. Real-time RT-PCR is a very sensitive, accurate and reproducible technique that can be used to detect very small amounts of RNA molecules, and it can therefore be applied for analysis of the expression of herpesvirus genes from the very early period of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 64 publications
(50 reference statements)
5
111
0
Order By: Relevance
“…Additionally, this technology has been proved to be effi cient for analysis of virus gene expression, for example, Eepstein-Barr virus (Pan et al, 2005) and pseudorabies virus (Tombacz et al, 2009). Zhang et al (2008a) reported one-step real time RT-PCR methods for quantifying RSV-CP gene in rice tissues and in SBPH.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this technology has been proved to be effi cient for analysis of virus gene expression, for example, Eepstein-Barr virus (Pan et al, 2005) and pseudorabies virus (Tombacz et al, 2009). Zhang et al (2008a) reported one-step real time RT-PCR methods for quantifying RSV-CP gene in rice tissues and in SBPH.…”
Section: Introductionmentioning
confidence: 99%
“…Us1(ICP22 in HSV) is also a regulatory gene, which is an odd-one-out, becausebased on previous experiments there is no consensus as to whether the PRV us1 gene is expressed in IE, E or L kinetics [27][28][29]. Interestingly, us1, similar to ie180 is located in the IR region of the genome; therefore PRV has two copies of us1 genes so as of ie180 gene.…”
Section: Genestranscriptionmentioning
confidence: 99%
“…Primers pairs were used as described previously [29]. Briefly, primer pairs was designed using the Primer Express program (Applied Biosystems) and the FastPCR Professional …”
Section: Primers For Reverse Transcription (Rt) and Polymerase Chain mentioning
confidence: 99%
“…KG), as described previously [21]. Briefly, after the cells had been collected by centrifugation and lysed by buffer containing chaotropic ions, the nucleic acids were docked to a silica column.…”
Section: Rna Preparationmentioning
confidence: 99%
“…H 2 O was included as a no-template control, and cDNA derived from the reverse-transcribed RNAs of non-infected cells was used as a negative mock-infected control. We applied SYBR Green-based real-time PCR because of the lower costs and simpler protocol than for TaqMan probe-based methods for instance [21]. It has recently been demonstrated that the SYBR-based method of detection is as sensitive and specific, and has a similar dynamic range to that of the TaqMan-based technique [81].…”
Section: Reverse Transcription (Rt)mentioning
confidence: 99%